High-Performance Broadband Photodetector with Lateral Contact of n+-Si Wafer by Two Asymmetric Work-Function Electrodes - Dahiya S.; Pandey U.; Hazra S.; Chakraborty R.; Pramanik S.; Maurya P.P.; Pal B.N. (My University, 2025)
A high-performance broadband photodetector (PD) has been fabricated by using a heavily doped n-type silicon substrate (n+-Si) in a lateral photodiode geometry. This self-biased photodiode fabrication required only two asymmetric work-function electrodes deposited on top of a clean n+-Si substrate. Specifically, LiF/Al and MoOx /Ag are used as electrodes where LiF and MoO3 work as n+-Si/electrode interface layers for Al and Ag electrodes respectively. These two electrodes have a work function difference of ≈1.1 eV which is measured by ultraviolet photoelectron spectroscopy study. Under dark, this lateral contact device shows a rectifying behavior with reverse-to-forward current ratio of ≈5.3 × 103 under ±1 V external bias. Moreover, this device shows a very high photoresponse with a dark-to-light current ratio (IL/ID) of 2.15 × 104 under white light illumination (600 W m−2) at −1 V operating voltage. Besides, the device shows external quantum efficiency (EQE) of ≈16.1% under self-biasing (Vext = 0 V) conditions which reaches to 30.2% at −1 V external bias, whereas the device has responsivity (Rλ) and detectivity (D) of 10.2 A W−1 and 9.1 × 1012 Jones, respectively under self-biasing condition. The peak responsivity (Rλ) and detectivity (D) of these devices reaches to 17.5 A W−1 and 1.6 × 1013 Jones under −1 V external bias. © 2024 Wiley-VCH GmbH.